Penggunaan Silika Fume Untuk Reduksi Semen Dengan Limbah Granit Sebagai Pengganti Agregat Kasar Terhadap Kuat Tekan Dan Kuat Tarik Beton - Aswanti, Rina; Sariman, Syahrul; Yuniarto, Eka (Program Studi Teknik Sipil Universitas Bosowa, 2024)
Concrete is a mixture of cement, sand, gravel, and water. In order to obtain good quality in the process, added ingredients, waste, or other materials with a certain ratio value are added. In this case, the use of granite waste as a substitute for coarse aggregate that is easy to find and the use of silica fume which aims to increase the compressive strength of concrete. The purpose of this study was to determine the effect of granite waste and silica fume, as well as the relationship between compressive strength and tensile strength of concrete with these variations. The percentage of granite waste and silica fume varied, ranging from 5%-10% granite waste and 0%, 7.5%, 15%, 22.5%, and 30% silica fume. Concrete testing was carried out after the concrete was 28 days old. The planned compressive strength is 25 Mpa. From the results obtained, the average normal concrete compressive strength was 27.69 Mpa and the average normal concrete tensile strength was 3.14 Mpa. The addition of 5% - 10% percentage granite waste and 0% silica fume obtained an average compressive strength of 27.74 Mpa and 27.65 Mpa, and an average tensile strength of 3.18 Mpa and 3.16 Mpa. The percentage of 10% granite waste and silica fume 7.5%, 15%, 22.5%, and 30% obtained average compressive strengths of 26.42 Mpa, 26.33 Mpa, 25.10 Mpa, and 25.01 Mpa respectively and average tensile strengths of 2.71 Mpa, 2.64 Mpa, 2.50 Mpa, and 2.41 Mpa respectively.